Knowledge domain and research trends for Gestational Diabetes Mellitus and nutrition from 2011 to 2021: a bibliometric analysis - Hu, Zhefang; Chen, Qianyi; Luo, Man; Ren, Yanwei; Xu, Jianyun; Feng, Lijun (Frontiers in Nutrition, 2023)
Abstract Objective: Nutrient management and lifestyle changes are the frontlines of treatment for all pregnant women diagnosed with Gestational Diabetes Mellitus (GDM). This study aimed to identify the global research architecture, trends, and hotpots of GDM and nutrition. Methods: We obtained publications from the sub-databases of Science Citation Index Expanded and Social Science Citation Index sourced from the Web of Science Core Collection database on January 4, 2022, using publication years between 2011 and 2021. CiteSpace software, VOSviewer, and Microsoft Excel 2019 were used to conduct the bibliometric analyses. Results: A growing publication trend was observed for GDM and nutrition, and this field has great potential. More GDM and nutrition research has been conducted in developed countries than developing countries. The top three authors with a high publication frequency, co-citations, and a good h-index were from the USA. There were the four studies of randomized controlled trials (RCTs) or meta-analyses of RCTs, as well as one review in the top five items of cited literature. Keywords were categorized into four clusters based on the keywords visualization. Conclusions: It is important to strengthen the collaboration between nations of different economies to produce more high-quality research on GDM and nutrition. It may be beneficial to further study the etiology, diagnosis, and treatment of GDM based on current results to provide a new perspective on GDM and nutrition.